“Properties of a Scale of Self-Care Behaviors Facing COVID-19: An Exploratory Analysis in a Sample of University Students in Huanuco, Peru“ - Ruiz-Aquino, Mely (2022)
“The general objective of this article was to construct and describe the psychometric properties of a scale of selfcare behaviors against COVID-19. It was a descriptive, cross-sectional, psychometric validation study of a scale created to measure self-care behaviors in relation to COVID-19 in a total sample of 333 probabilistically selected. Qualitative validity was evaluated by a review of 10 experts and quantitative validity by means of exploratory factor analysis using the principal components method. Internal consistency was measured with Cronbach’s alpha twice and the test-retest was evaluated by calculating the intraclass coefficient. The final scale consisted of 29 items. The Kaiser-Meyer-Olkin test of adequacy yielded a value of 0.926, and the Bartlett’s test of sphericity X² = 4611 with a p-value < 0.001. The variance explained by the three retained factors with a total of 29 items was 50.03%. The Cronbach’s alpha internal consistency evaluation yielded an initial value of 0.923 and, in a second evaluation, showed a value of 0.936. In addition, the intraclass coefficient in the test-retest yielded a value of 0.929. The instrument created and validated possessed the necessary conditions as a useful and reliable tool for measuring self-care behaviors in relation to COVID-19 in a population of university students and it is important that it can be applied in other regions of the world.“